Guide :

# can soeone help.ASAP 5(7-4)-6 to the second power +3+1

Need help asap

## Research, Knowledge and Information :

### 2017 NBA mock draft and lottery results - MSN

2017 NBA mock draft and lottery results. ... Smith is my second ... but Oklahoma City might prefer to take a 21-year-old who can contribute as soon as possible ...

... Through the power of ... (x/4)-5 English writing Please ASAP can someone give me an introductory ... Alegebra 1 can someone please help me asap with this two ...

... there are 60 million students who want to help each other learn. ... Can someone please answer this asap? Download png. 1. ... = -5 * 3 to the power of x-1 Answer ...

Download Business trial ASAP Utilities 7.3.1 (30.7 MB) Can't ... On average ASAP Utilities saves people 30.6 ... on the ASAP Utilities website. Need help with ...

### What would control one bank and not the other - ASAP

I have an intermediate missfire on cylinders 1, 3, 5, and 7, but mostly 1 and 3. ... on the second consecutive ignition cycle that the ... power and ground circuits ...

### I need someone who is VERY good at Photo Shop to help me ASAP ...

It is very easy and will only take a second.. ... rails programmer help asap, i need a good photo editor person, ... and I believe I can help you to ...

math i need help on arrays and an expanded algorithm please wright as asap please math asap I don't understand can you please help bedtime 1. (-5)-(-6)+(-1) 2.

## Suggested Questions And Answer :

### can soeone help.ASAP 5(7-4)-6 to the second power +3+1

???????????? 5*(7-4)-6^2 +3+1 ?????????? 5*3 -36 +4 15+4-36 19-36 -17

### x to the second power minus 2 x y plus 4y to the second power

x to the second power minus 2 x y plus 4y to the second power This comes out as: x^2 - 2y + (4y)^2

Group similar powers of X together so we have -15+2+10=-3X^2. The expression now becomes 11X^3-3X^2-3X. X is a common factor: X(11X^2-3X-3). The quadratic doesn't factorise further.

### How do i solve this? x^2 +5x +6 = 2

Problem: How do i solve this? x^2 +5x +6 = 2 The first number is x squared to the second power. The first number is x squared, also called x to the second power. It is NOT x squared to the second power. That would be x^4. x^2 + 5x + 6 = 2 x^2 + 5x + 6 - 2 = 2 - 2 x^2 + 5x + 4 = 0 (x + 4)(x + 1) = 0 One or both must be zero. x + 4 = 0 x = -4 x + 1 = 0 x = -1 Check. x^2 + 5x + 6 = 2 (-4)^2 + 5(-4) + 6 = 2 16 - 20 + 6 = 2 2 = 2 x^2 + 5x + 6 = 2 (-1)^2 + 5(-1) + 6 = 2 1 - 5 + 6 = 2 2 = 2 Answer: x = -4  and  x = - 1

### simplify the negative exponents 5 negative one power and 4 negative second power ?

To find the answer you just need to find the number to the power without a negative and put it under a fraction bar with 1 over it. 5 to the negative first= 1/5 and 4 to the negative second= 1/16

### what does x second power - 4 second power= the square root of 15 to the second power equal

"square root av fifteen tu the sekond power"...15

### 1. x to the second power + 6x +9 2. 4x to the second power +20x + 25 3. 36x to the second power - 24x +16

?????????? did yu tri tu sae "x^2 +6x+9.2=0" ??????????? quadratik equashun giv roots=-3+-0.447213595i (komplex variabels) b^2-4ac=-0.8, so sqrt(-0.8) giv 0.894427191i

### what is 1 x 10 to the second power divided by 1 x 10 to the negative third power?

10^2/ 10^-3=10^2 * 10^3=10^5=1e5

### 2x to the third power + 3x to the second power - 8x = 12

2x^3 + 3x^2 - 8x = 12 this is a cubic equation so set f(x) = 2x^3 + 3x^2 - 8x - 12 = 0 and search for roots. f(0) = -12,   negative f(1) = -15,   more negative f(2) = 16 + 12 - 16 - 12 = 0 -- a root has been found. (x - 2) is a factor of f(x), so divide f(x) by (x-2), giving (x - 2)(2x^2 + 7x + 6) = 0    and the quadratic here factorises to give, (x - 2)(2x + 3)(x + 2) = 0 So the solutions are: x = 2, x = -3/2, x = -2

### 1.5 divided by(0-1) to the second power x 2 =

(1.5 / ((0 - 1) to the second)) x 2 = 3   Answer: 3